The Determinants of Indonesia's Processed Wood Export Performance - Feridah Feridah; Darwati Susilastuti; Pudji Astuty (PT. Publikasiku Academic Solution, 2026)
In the context of domestic supply-side constraints and fluctuating global demand, the Indonesian processed wood export sector is confronted with substantial obstacles. Although Indonesia has sizable forest resources, the export performance of processed timber products has varied significantly among provinces between 2016 and 2024, as a result of a variety of logistical and production factors. The objective of this investigation is to evaluate the export performance of Indonesian processed wood products in the context of domestic processed wood production, forestry and wood processing investment, educated labor in the forestry sector, and logistics infrastructure. Panel data regression analysis is implemented in the investigation. The sample was comprised of 11 provinces in Indonesia that were observed annually from 2015 to 2024. The data was obtained from the Ministry of Environment and Forestry, the Ministry of Investment/BKPM, and Statistics Indonesia (BPS). The results of the panel data regression indicate that domestic processed wood production, forestry and wood processing investment, educated labor in the forestry sector, and logistics infrastructure simultaneously have a significant effect on the export performance of processed wood products. Partially, each independent variable also demonstrates a significant and positive influence on export performance. These findings suggest that increasing domestic production capacity, attracting investment to the forestry sector, developing a skilled workforce, and improving logistics infrastructure are key determinants in enhancing Indonesia's competitiveness in global processed wood markets